Dose–Response Relative Risk of Injury From Acute Alcohol Consumption in 22 Countries: Are Women at Higher Risk Than Men? - Cherpitel, Cheryl J (Alcohol Alcohol, 2019)
AIMS: The risk of injury from alcohol consumption was analyzed by gender, controlling for frequency of heavy drinking occasions, and by cause of injury (traffic, violence, fall, other). METHODS: Case-crossover analysis was conducted on 18,627 injured patients arriving at the emergency department (ED) within six hours of the event. FINDINGS: Risk of injury was similar for females and males at ≤3 drinks prior to injury (OR = 2.74 vs. 2.76, respectively). At higher volume levels females were at greater risk than males, and significantly so at 3.1–6 drinks and 6.1–10 drinks (gender by volume interaction: OR = 0.60, CI = 0.39–0.93 and OR = 0.50, CI = 0.27–0.93, respectively). For those reporting 5+ ≥ monthly, females were at higher risk than males at all volume levels, and the gender by volume interaction was stronger than for those consuming 5+ <monthly at ≤3 drinks (OR = 0.51, CI = 0.28–0.92) and 6.1–10 drinks (OR = 0.39, CI = 0.18–0.82). Females were at higher risk of injury than males for all causes of injury except those related to traffic at lower levels of consumption (<6 drinks), although the gender by volume interaction was significant only for injury from other causes at 3.1–6 drinks (OR = 0.23, CI = 0.09–0.87). CONCLUSIONS: Females are at higher risk of injury than males, regardless of frequency of heavy drinking and for all causes other than those related to traffic.